(untitled) (Jurnal Manajemen dan Ekonomi (JME), 2023)
Visionary leadership is a type of leadership that emphasizes the ability of a leader to formulate and communicate a clear and attractive long-term vision to organizational members. Visionary leaders have the ability to provide specific directions and motivate organizational members to achieve the goals set. They are also able to identify and address changes and challenges that the organization may face in the future. Meanwhile, organizational performance is the ability of the organization to achieve the goals that have been set. Organizational performance can be measured from various perspectives, such as productivity, efficiency, profitability, and customer satisfaction. Good organizational performance can help organizations to maintain competitiveness and achieve long-term goals. Research has shown that visionary leadership can have a positive influence on organizational performance. Visionary leaders who are able to formulate and communicate a strong vision can help direct and move members of the organization in achieving the goals set. Visionary leadership can also provide a high sense of confidence and involvement in employees, as well as provide a long-term view that can help them understand the overall goals of the organization. Overall, visionary leadership can be an important factor in achieving an organization’s long-term goals and improving overall performance.